2014
DOI: 10.3349/ymj.2014.55.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Early Feeding Is Feasible after Emergency Gastrointestinal Surgery

Abstract: PurposeThis study was undertaken to assess the feasibility of early feeding in patients that have undergone emergency gastrointestinal (GI) surgery.Materials and MethodsThe authors retrospectively reviewed 84 patients that underwent emergency bowel resection and/or anastomosis from March 2008 to December 2011. Patients with severe shock, intestinal ischemia, sustained bowel perforation, or short bowel syndrome were excluded. Patients were divided into the early (group E; n=44) or late (group L; n=40) group acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
0
12
0
11
Order By: Relevance
“…timing, volume, assessment of nutritional efficacy, tolerance to feeding and method of nutrition delivery (McClave et al , ). Randomized controlled trials and meta‐analyses have shown improved patient outcomes when enteral nutrition was delivered within 24–48 h of admission to ICU (Marik and Zaloga, ; Doig et al , ; Khalid et al , ; Chiang et al , ; Vicic et al , ; Lee et al , ; Li et al , ; Kim et al , ; Yin et al , ; McClave et al , ). Specifically, there was a significant reduction in mortality and infectious complications across multiple patient populations (Marik and Zaloga, ; Doig et al , ; Khalid et al , ; McClave et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…timing, volume, assessment of nutritional efficacy, tolerance to feeding and method of nutrition delivery (McClave et al , ). Randomized controlled trials and meta‐analyses have shown improved patient outcomes when enteral nutrition was delivered within 24–48 h of admission to ICU (Marik and Zaloga, ; Doig et al , ; Khalid et al , ; Chiang et al , ; Vicic et al , ; Lee et al , ; Li et al , ; Kim et al , ; Yin et al , ; McClave et al , ). Specifically, there was a significant reduction in mortality and infectious complications across multiple patient populations (Marik and Zaloga, ; Doig et al , ; Khalid et al , ; McClave et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…(13) Já está estabelecido na literatura que a instituição precoce e adequada da TN pode diminuir a morbidade de pacientes graves em UTI. (1)(2)(8)(9)(14)(15)(16)(17)(18) .…”
Section: Discussionunclassified
“…(9) Além disso, evidências revelam outros benefícios quanto ao início precoce da TNE como redução estatisticamente significativa na mortalidade e desenvolvimento de pneumonia, complicações infecciosas em geral e tempo de internação hospitalar. (14,(16)(17)(18) Gordon S. Doing et al (2009) confirmam essas evidências na meta-análise realizada sobre ensaios clínicos metodologicamente validados pela revisão sistemática da literatura, em que revelam uma redução significativa na mortalidade e pneumonia atribuível à disposição da introdução precoce da TNE no prazo de 24 horas de admissão em UTI. (19) Apesar das evidências e de especialistas ressaltarem a importância do início de TN no prazo de 24 horas a 48 horas de admissão em UTI, na prática clínica é diferente.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A retrospective study on 84 patients who had emergency bowel resection and/or anastomosis reported that early enteral feeding was feasible in hemodynamically stable patients [48]. A randomized trial compared early oral feeding (within 24 hours) to traditional postoperative feeds advancement and found no differences in complication rates, postoperative ileus, or length of hospital stay.…”
Section: Traditions and Dogmasmentioning
confidence: 99%